2014
DOI: 10.1021/jp5052563
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-Templated Growth of Pd Nanoclusters

Abstract: Graphene grown on Rh(111) was used as a template for the growth of Pd nanoclusters. Using high-resolution synchrotron radiation-based X-ray photoelectron spectroscopy, we studied the deposition of Pd on corrugated graphene in situ. From the XP spectra, we deduce a cluster-by-cluster growth mode. The formation of clusters with 3 nm diameter was confirmed by low-temperature scanning tunneling microscopy measurements. The investigation of the thermal stability of the Pd particles showed three characteristic tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
50
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(56 citation statements)
references
References 32 publications
6
50
0
Order By: Relevance
“…Subsequently, Pt was deposited by electron beam evaporation. The Moiré structure of the lattice-mismatched graphene thereby serves as template for the formation of nanoclusters [3,7]. Selected S 2p spectra measured during adsorption of SO 2 on 0.7 ML Pt/Gr/ Rh(111) at 150 K are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, Pt was deposited by electron beam evaporation. The Moiré structure of the lattice-mismatched graphene thereby serves as template for the formation of nanoclusters [3,7]. Selected S 2p spectra measured during adsorption of SO 2 on 0.7 ML Pt/Gr/ Rh(111) at 150 K are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, a model system on a chemically inert support material is desirable. Recently, the fabrication of nano-cluster arrays using the template effect of the graphene Moiré structure on lattice-mismatched substrates has been explored in detail [3][4][5][6][7]. These nanocluster arrays are intriguing model systems for catalysis due to the small size distribution of the metal particles, on a chemically innocent support.…”
Section: Introductionmentioning
confidence: 99%
“…One successful route to efficiently study the properties of metal clusters is to prepare ordered nanocluster arrays on corrugated templates such as the 2D materials graphene or hexagonal boron nitride ( h‐ BN) on certain transition metal surfaces. Due to the lattice mismatch, lateral differences in the strength of interaction between the 2D material and the metal surface occur, leading to a regularly corrugated Moiré‐patterned nanosheet [21–24] . Metal nanocluster arrays deposited onto such ordered structured substrates have a narrow size distribution and thus serve as model catalysts, representing an innovative approach to overcome the material gap to commercial catalysts [25,26] .…”
Section: Introductionmentioning
confidence: 99%
“…Graphene may o↵er a high degree of control over the arrangement and separation of nanoclusters, allowing templated growth of systems with specific cluster topologies and electronic structures. [6][7][8][9][10][11][12][13][14][15] The electronic interactions between graphene and the guest material play a central role in the early growth process. 16,17 A Monte Carlo study conducted by Guo et al 12 on ZnO nanoparticle growth on graphene showed that the deformation of Zn clusters and layering on the graphene provides suitable nucleation sites governed mainly by Zncarbon bond formation.…”
Section: Introductionmentioning
confidence: 99%